Responsabilidade pelo fato do produto tóxico no direito nos Estados Unidos e no Brasil - Atz, Ana Paula (Universidade do Vale do Rio dos Sinos, 2018)
Consumer Law - a field of law that studies and provides legal responses to damages caused by defective products - faces challenges imposed on products conceived nowadays in a massified, industrialized and global risk-taking society. From this perspective, the scenario of toxic products faces a new dilemma of Consumer Law: how to act in the present, given the uncertainty and unpredictability of the consequences and adverse effects of a product, through a formula of legal certainty? This study addresses the following research problem: what are the appropriate standards to adopt in verifying the causal link in cases involving responsibility for the fact of the toxic product? To this end, it intends to establish the legal bases for obtaining answers in a context of scientific uncertainties concerning the problem of causes and effects of toxic substances. The comparative study of the laws of the United States and Brazil on the subject and also on the cases related to the drug Vioxx and the asbestos substance judged in both countries was promoted. It was also chosen as a method of approach by the pragmatic-systemic methodology, which allows the realization of second order observations, and with this, the description of the operability of other systems of society beyond Law, such as the Science system. The product liability related to toxic product in Brazilian Consumer Law advocates a new way for legal operators to access the causal nexus based on probabilistic judgments, taking into account the broadening of the dialogue with scientific studies for the measurement of scientific sufficiency, the causal inference and the differentiated role of the experts, both in the specialization and in the methodology used. The design defect and failure to warn, therefore, encompasses new contours and thus requires an increase in the duty of diligence on the part of the supplier, since, as an expert in the product, he should act as the main interested in unveiling and accompanying scientific studies on the adverse effects of the product on human health.

La loi des consommateurs - zone de droit d'étudier et permet des réponses juridiques aux dommages causés par des produits défectueux - défis face à des produits conçus en notre temps dans une société de masse, industrialisés et producteurs des risques mondiaux. Dans cette perspective, la mise des produits toxiques sont confrontés à un nouveau dilemme à la loi des consommateurs: comment agir dans le présent, face à l'incertitude et l'imprévisibilité des conséquences et des effets néfastes d'un produit par la sécurité juridique de formule? Cette étude aborde le problème de recherche suivant: quelles sont les normes appropriées à adopter pour vérifier le lien de causalité dans les cas impliquant une responsabilité pour le fait du produit toxique? À cette fin, il entend établir les bases juridiques permettant d'obtenir des réponses dans un contexte d'incertitudes scientifiques concernant le problème des causes et des effets des substances toxiques. a été promu alors l'étude comparative des lois des États-Unis et le Brésil sur le sujet et aussi les cas pertinents à la drogue Vioxx et de la substance de l'amiante, essayé dans les deux pays. Une décision a également méthode d'approche par la méthodologie pragmatique systémique, ce qui permet la réalisation d'observations de second ordre, et donc, la description du fonctionnement des autres systèmes de la société au-delà de la loi, comme le système scientifique. La responsabilité du fait que le produit toxique sur le droit de la consommation brésilienne préconise une nouvelle façon pour les professionnels du droit d'accéder un lien de causalité fondées sur des jugements probabilistes, en tenant compte de l'élargissement du dialogue avec les études scientifiques pour la mesure de la suffisance scientifique , l'inférence causale et le rôle différencié des experts, tant dans la spécialisation que dans la méthodologie utilisée. Les défauts de conception et de l'information comprend donc de nouveaux contours et nécessite donc de plus en plus l'obligation de diligence, par le fournisseur, puisque, en tant qu'expert dans le produit, il devrait agir comme principal intéressé à découvrir et accompagner les études scientifiques sur les effets néfastes du produit sur la santé humaine.
Keywords: Responsabilidade pelo fato do produto tóxico; Teoria da causalidade adequada; Estudos epidemiológicos; Admissibilidade do expert; Defeito de informação; Toxic product liability; Theory of proper causality; Epidemiological studies; Admissibility of the expert; Failure to warn; Responsabilité du fait du produit toxique; Théorie de la causalité appropriée; Etudes épidémiologiques; Admissibilité de l'expert; Échec de l'information; ACCNPQ::Ciências Sociais Aplicadas::Direito